Role of the CXCL13/CXCR5 Axis in Autoimmune Diseases - Pan, Zijian; Zhu, Tong; Liu, Yanjun; Zhang, Nannan (Frontiers in Immunology, 2022)
CXCL13 is a B-cell chemokine produced mainly by mesenchymal lymphoid tissue organizer cells, follicular dendritic cells, and human T follicular helper cells. By binding to its receptor, CXCR5, CXCL13 plays an important role in lymphoid neogenesis, lymphoid organization, and immune responses. Recent studies have found that CXCL13 and its receptor CXCR5 are implicated in the pathogenesis of several autoimmune diseases, such as rheumatoid arthritis, multiple sclerosis, systemic lupus erythematosus, primary Sjögren’s syndrome, myasthenia gravis, and inflammatory bowel disease. In this review, we discuss the biological features of CXCL13 and CXCR5 and the recent findings on the pathogenic roles of the CXCL13/CXCR5 axis in autoimmune diseases. Furthermore, we discuss the potential role of CXCL13 as a disease biomarker and therapeutic target in autoimmune diseases.